Direct instruction model assisted with PhET and Whatsapp to students' cognitive and motivation. (February 2020) - Oktavia, F; Muhibbuddin,; Mursal,
Abstract: This research aims at understanding the influence of the direct instruction learning model assisted with PhET and WhatsApp media to students' cognitive and motivation in studying gas kinetic theory at State Senior High School 3 of Banda Aceh. The population in this study was all science department students at year 11 divided into 5 classes. While the sample of the study was two classes that were selected using a random sampling technique. Data were collected by providing test and non-test. The obtained data were normal and homogeneous. Thus, it can be analyzed using the t-test to measure learning outcomes. To indicate the difference between experimental class and control class, it was used the t-test for questionnaire. Pretest has ttest = 1.27 which its value is less than ttable. In conclusion, there is any significant difference between the experimental class and the control class. In addition, both classes revealed the same difference for the pretest. The posttest also showed the significant difference according to tcount = 5.5 which is greater than ttable. Therefore, it can be concluded that there is any difference, which students' cognitive experimental class is greater than the control class.